Master‐Slave Pixel Concept Used for Improved Sensor‐Display Array Circuits on Flexible Substrates. Issue 1 (June 2014) - Papadopoulos, Nikolas P.; Lee, Czang‐Ho; Wong, William S.
Abstract A proposed master‐slave sensor‐display pixel concept for compensating the output current's peaks in a sensor/display pixel circuit is described. The circuits consists of two main parts: a master light‐sensor pixel and slave display pixels, which are driven directly from the master sensor pixel within a TFT backplane array. a‐Si:H TFTs on plastic substrates were used as the dual photosensor/switching device. Simulations show that the display pixels maintain a wide output current operating range from a few nA in the dark and up to 1.6uA output during white‐light illumination of ~0.3mW/cm2.